(untitled) (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
This report discusses a social work intervention in a child abuse case handled by the UPTD PPA of North Sumatra Province. The social worker implemented the stages of social work practice, including engagement, assessment, planning, intervention, evaluation, and termination. The intervention was also guided by Maslow’s Hierarchy of Needs theory, which helped in understanding and addressing the child’s needs—from basic needs such as safety and shelter to psychological needs through counseling and family mediation. Although the intervention was supported by institutional procedures, challenges such as the child’s emotional trauma and lack of family support persisted. This report highlights the importance of a multidisciplinary approach, continuous monitoring, and collaboration among institutions to ensure the child’s safety and holistic recovery. This case illustrates the vital role of professional social work in protecting children’s rights and supporting their healing process in a safe and supportive environment.